2023
DOI: 10.1021/acsaem.3c00151
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Urea and Ethanol on Two-Dimensional Amorphous Nickel Oxide Encapsulated on N-Doped Carbon Nanosheets

Abstract: Hydrogen production from water electrolysis is of great interest for attaining sustainable clean energy storage and conversion, but the required working voltage (>1.23 V) in water splitting limits its applications in industrial expansion. Therefore, replacing the oxygen evolution reaction (OER) with a more favorable anodic oxidation reaction, which can provide more valuable products and less working voltage, will be of great significance for the upcoming expansion of hydrogen production in industrial applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The results showed that the cell using NiO x /CN x needed only 1.414 V cell potential to achieve 20 mA/cm 2 current density, whereas 1.626 V was required for overall water electrolysis. This demonstrates the good catalytic activity of NiO x /CN x in ethanol oxidation …”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 58%
See 1 more Smart Citation
“…The results showed that the cell using NiO x /CN x needed only 1.414 V cell potential to achieve 20 mA/cm 2 current density, whereas 1.626 V was required for overall water electrolysis. This demonstrates the good catalytic activity of NiO x /CN x in ethanol oxidation …”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 58%
“…It is generally recognized that employing an appropriate carbon-based support to anchor nanocatalysts is an effective strategy for enhancing their catalytic properties in ethanol oxidation. This approach offers a promising approach to enhance the overall activity of catalysts in this reaction. , Recently, we reported a 2D amorphous NiO/N-doped carbon nanosheet (NiO x /CN x ) for the purpose of ethanol oxidation coupled with hydrogen (H 2 ) production . The performance of NiO x /CN x was evaluated through ethanol electrolysis in a two-electrode configuration, where NiO x /CN x -coated carbon cloth was used as the anode and commercial Pt/C-modified carbon cloth was used as cathode.…”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 99%
“…2b shows the high-resolution Ni 2p spectra of Cu/NiO-NF and NiO-NF, in which for Cu/NiO-NF and NiO-NF, the peaks at 854.3, 872.1, 861.6 and 879.4 eV are attributed to Ni 2+ 2p3/2, Ni 2+ 2p1/2, and two satellite peaks of typical NiO, respectively. 34,35 The two peaks at 856.1 and 873.9 eV can be attributed to Ni 3+ in the 2p3/2 and 2p1/2 regions, respectively, which are produced by negatively charged surface oxygen. 36 It is worth noting that the binding energy of the characteristic peak of Ni 2+ of Cu/NiO-NF shifts 0.4 eV towards the higher binding energy relative to that of NiO-NF, which is due to the strong interfacial electron interaction between NiO and Cu, indicating that nickel is an electron donor.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, nickel-based catalysts are found to be the most reported, thanks to their promising properties in the urea oxidation reaction in an alkaline medium. , The presence of nickel with high valency (Ni 3+ ) was identified as one of the key features of the active urea oxidation reaction catalysts . Unfortunately, owing to the durability and relatively poor stability of nickel-based materials, they are still far from commercialization in urea-based technologies. , …”
Section: Introductionmentioning
confidence: 99%